Status of the fishery of jaffna lagoon, sri lanka - Ragavan, N.; Dissanayake, D.C.T.; Kuganathan, S. (University of Jaffna, 2021)
Jaffna lagoon (9° 50' N and 79° 50' E to 9° 20' N and 80° 30' E) is the largest lagoon in Sri Lanka and it provides many services including fishing opportunities to the people in northern Sri Lanka. However, the status of the Jaffna lagoon fishery is not fully known at present due to the lack of detailed studies over the last 40 years. Therefore, this study was designed to fulfil this research gap. Both primary data and secondary data were used in this study. Primary data, including catch and fishing effort were collected at three major landing sites, Gurunagar, Paasaiyoor, and Kachchai by making fortnight field visits from March to December 2019. Secondary data of the monthly total catch and fishing effort were obtained from the district fisheries offices in Jaffna and Kilinochchi districts in order to estimate MSY and FMSY. This study revealed that ~5340 fishers confined to 39 landing sites were actively engaged in lagoon fishing during the study period using 12 different fishing methods. Fyke nets (71%) followed by stake nets (10%), lagoon seines, and lagoon boat seines (6%) are the widely used fishing methods in lagoon fisheries. Catch rates of major fishing gear were calculated and recorded as kg fisherman-1 , day-1 . Stake net (37kg ± 7) reported a significantly higher catch rate than fyke net (18kg ± 3), seine net (17kg ± 6), and crab net (16kg ± 3) (p<0.05; ANOVA). Both mechanized (59%) and non-mechanized (41%) crafts are used in the lagoon fishing practices. Forty-six commercially important finfish and shellfish species belonging to 25 families were identified in the lagoon catches of which Penaeidae made the highest percentage contribution (27%), followed by Siganidae (13%), Mugilidae (11%), Lethrinidae (10%), and Gerreidae (9%). Analysis of secondary data confirmed the increasing trend of fishing effort since 2009 but the total landings declined gradually after reporting its maximum value of 6958 Mt. in 2012. A rough estimate of maximum sustainable yield of the fishery of Jaffna lagoon was 6,694 Mt with the annual fishing effort (FMSY) of 1007 crafts. As the current fishing effort is higher than the FMSY, input control measures are recommended to utilize the lagoon fishery resources in a sustainable manner.
Keywords: Jaffna lagoon; Catch rate; Fishing methods; Maximum sustainable yield